Plantae Austro-Americanae, II: De investigationibus generis Herrania diversae observationes Plantae Austro-Americanae, II: De investigationibus generis Herrania diversae observationes - Schultes Richard Evans (Caldasia)
The following observations are presented as a result of revisionary studies in the sterculiaceous genus Herrania. The following observations are presented as a result of revisionary studies in the sterculiaceous genus Herrania.